Limnospira fusiformis from Lake Solenoe, Omsk: Rationalizing Marketing and Research - Elena A. Moliboga; Viktoriya V. Leushkina (Техника и технология пищевых производств)
A diverse food product range makes the consumer more demanding and pickier in terms of choice, safety, and price. As a result, food producers turn to alternative protein sources, such as microalgae. Microalgae are rich in protein (60%), unsaturated fatty acids, and other nutrients. The article describes the consumer preferences and patterns in the city of Omsk, Russia, regarding spirulina-containing products. The research objective was to determine the marketing and research prospects for Limnospira fusiformis phytomass. The authors used both experimental and marketing methods to study the range of spirulina-containing products on the food market of Omsk and its surroundings. The marketing survey involved 1000 Omsk residents. According to the survey, 19.2% bought spirulina-containing products regularly; 20.8% bought them at least once a week; 79.2% consumed spirulina as dietary supplements. The respondents explained their choice by the composition and certification data (58.4%), as well as by health care reasons (75.3%); 48.1% preferred online platforms; 42.9% studied the pricing policy before purchasing. The survey revealed two distinct profiles of an average spirulina consumer. The resulting roadmap for spirulina marketing in the Omsk Region included the following steps: promotion; scientific and technical documentation; technical and economic production indicators; pricing; technological optimization. The marketing research revealed a number of socio-economic effects of introducing spirulina products to the local food market, which included economic, social, environmental, scientific, resource, and budgetary consequences. The two profiles of an average spirulina consumer from the Omsk Region made it possible to develop some recommendations for local spirulina producers and businesses.